Integrated rural accessibility Planning: feasible option for rural access planning in Nigeria (2009)
Rural roads are crucial to the socio-economic development of the rural inhabitants. It provides them the opportunity to access water and firewood points, farm plots and educational and health facilities among others. However; the state of rural roads in Nigeria is deplorable with about 75% of them in poor condition. The consequence is that the rural communities are cut off from socio-economic facilities resulting in perpetuation of rural poverty. Efforts geared towards rural access planning over the years in Nigeria relied on top-down approach and qualitative assessment of the travel characteristics of the rural people. The result is the dismal failure of the approach to provide sustainable solutions to the mobility constraints of members of rural communities. Therefore, the adoption of Integrated Rural Accessibility Planning, an approach that is quantifiable, need-based and participatory (bottom-up) in addressing the rural access problem of the rural people may be the option needed for solving the seemingly intractable rural accessibility constraints in the rural areas in the country.